Effects of a Novel Magnesium-L-Theanine Compound on Brain Electrical Activity in Mice - Dasdelen, Muhammed Furkan; Er, Sezgin; Celik, Suleyman; Kaplan, Berkan; Komorowski, James; Şahin, Kazım; Kilic, Ertugrul (Wiley, 2022)
[Abstract Not Available]
Keywords: Caffein; ECoG; L-Theanine; Mg-Threonate; Sleep Disturbance